PENGARUH PEMBERIAN AMELIORAN ORGANIK TERHADAP PERTUMBUHAN TIGA JENIS ANAKAN - Novitri Hastuti; Djeni Hendra; R. Esa Pangersa Gusti (BRIN Publishing, 2018)
The availability of organic ameliorants is very important to induce seedling growth. This study examines the effect of various organic ameliorant addition into the growth of kemenyan seedlings (Styrax benzoin Dyrand), trembesi (Samanea saman Jack. (Merril.) ) and ki bawang (Melia excelsa Jack). The addition of organic ameliorants were grouped into 11 different treatments: (p) soil (control); (q) charcoal organic fertilizer (POA) 10%; (r) POA 10%+ charcoal sawdust (ASG) 5%; (s) POA 10% +ASG 10%; (t) organic fertilizer tablet of charcoal and mycorrhiza (POAM); (u) organic fertilizer tablet of mycorrhiza (POM); (v) POM + ASG 5%; (w) wood vinegar (CK) 1%; (x) CK 1% + ASG 5%; (y) CK 2%; (z) CK 2% +ASG 5%. The Results showed that treatment r, the use of 10% charcoal organic fertilizers (POA) and5% charcoal sawdust (ASG) affected most significantly to the height increments. The analysis of variance showed that the various treatment of ameliorant addition affected significantly to height increments but did not have significant effect to the diameter increments.